Z zagadnień teleologii dydaktyki wartości o celach i materiale wychowania literackiego = From the problems of teleology of values didactics. The objectives and material of literary education. - Pasterniak, Wojciech (1935-2018); Pasterniak, Lilla (Zielona Góra: Wyższa Szkoła Pedagogiczna)
The paper is concerned with the aims and materials of the literary education. It discusses two basic strategies of education, namely the strategy called "culture makes man" and the strategy described as "man makes culture". The paper stresses that the final result of the literary existence and education is "the humanity". The detailed discussion of the philasophy of education constitutes the background for presenting the following objectives of the literary education realized in - recognizing, - comprehending, - accepting and - respecting the artistic, aesthetic and beyond - aesthetic values.
Keywords: teleologia; dydaktyka wartości; dydaktyka literatury